2020
DOI: 10.3389/fpsyt.2020.573410
|View full text |Cite
|
Sign up to set email alerts
|

Recent/Childhood Adversities and Mental Disorders Among US Immigrants

Abstract: Past research documents the heterogeneity in US immigrants, particularly in terms of racial and ethnic categories and specific ethnic subgroups. The present study builds on this research foundation by investigating heterogeneity in immigrants' experiences of adversity, both recent and during childhood, and associations with mental disorders. Data are drawn from 6,131 adult immigrants in the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions-III. Prevalence estimates for mental disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…This finding is particularly important and highlights the fact that Arab American young adults may experience multiple social adversities early in their life. Studies among other immigrant adults/young adults reported that individuals who experience multiple adversities early in life are more prone to mental health problems later in their life (Cano & Takeuchi, 2020; Hagan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly important and highlights the fact that Arab American young adults may experience multiple social adversities early in their life. Studies among other immigrant adults/young adults reported that individuals who experience multiple adversities early in life are more prone to mental health problems later in their life (Cano & Takeuchi, 2020; Hagan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies focus on in depth research of specific trauma experiences of women immigrants [19]. Some studies have focused on the impacts of exposure to trauma and mental health among Latinx immigrants [11,[20][21][22], though few have studied exposure to trauma among recent Latinx immigrants [23,24]. The rationale for our study is that we present a first time comparison of traumatic experiences of recent immigrant adults from Latin America by sex and place of occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies focus on in depth research of specific trauma experiences of women immigrants [19]. Some studies have focused on the impacts of exposure to trauma and mental health among Latinx immigrants [11,[20][21][22], though few have studied exposure to trauma among recent Latinx immigrants [23,24]. The rationale for our study is that we present a first time comparison of traumatic experiences of recent immigrant adults from Latin America by sex and place of occurrence.…”
Section: Introductionmentioning
confidence: 99%